Kinetic and spatiotemporal characteristics of running during regular training sessions for collegiate male distance runners using shoe-based wearable sensors - Long, T.; Pavicic, P.; Stapleton, D. (Journal of Athletic Training, 2023)
Context Assessment of running mechanics has traditionally been conducted in laboratory settings; the advancement of wearable technology permits data collection during outdoor training sessions. Exploring changes in running mechanics across training-session types may assist runners, coaches, and sports medicine clinicians in improving performance and managing the injury risk.